Prediction of Financial Distress in Manufacturing Company: A Comparative Analysis of Springate Model and Fulmer Model - Raid Ayasy Shalih; Fariyana Kusumawati (JAFFA, 2019)
This research aims to analyze the differences in financial distress predictions between the Springate model and the Fulmer model. The method used in this research is quantitative. The type of data used in this research is secondary data in the form BEI of company financial statements for 2014-2016. The data analysis technique uses the One Way ANOVA test. The results showed that there are significant differences between the Springate model and the Fulmer model in predicting financial distress in manufacturing companies listed on the Indonesia stock exchange during 2014-2016. The most relevant model in predicting financial distress in this study is the Springate model.